The use of opioids in chronic nonmalignant pain - Hilgier, Maciej (Przewodnik Lekarza/Guide for GPs, 2006)
The majority of patients with cancer pain need therapy including strong opioids, and patients with non-cancer pain may also benefit from strong opioid medication. The use of opioid analgesics for long term management of chronic non-cancer pain is now an accepted, although still a controversial medical practice. The controversy surrounding the long-term use of opioid drugs in patients with nonmalignant pain has intensified in recent years. This debate is driven by a new willingness to consider the potential benefits of an approach that has been traditionally rejected as invariably ineffective and unsafe. In fact long-term medication with strong opioids is much safer than with NSAIDs. Implementation strong opioids to chronic non-malignant pain treatment need clear-cut guidelines. Such exists in USA and in many countries in Europe. The Polish guidelines are presented and discussed in the article.